1993
DOI: 10.1083/jcb.121.5.1181
|View full text |Cite
|
Sign up to set email alerts
|

Type V collagen: molecular structure and fibrillar organization of the chicken alpha 1(V) NH2-terminal domain, a putative regulator of corneal fibrillogenesis.

Abstract: Abstract. Previous work from our laboratories has demonstrated that: (a) the striated collagen fibrils of the corneal stroma are heterotypic structures composed of type V collagen molecules coassembled along with those of type I collagen, (b) the high content of type V collagen within the corneal collagen fibrils is one factor responsible for the small, uniform fibrillar diameter (25 nm) characteristic of this tissue, (c) the completely processed form of type V collagen found within tissues retains a large non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
214
0
7

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(228 citation statements)
references
References 46 publications
(63 reference statements)
3
214
0
7
Order By: Relevance
“…We observed collagen fibrils with an ordered and regular barbed appearance in the myometrium (Fig. 2B), which resembles that observed in chick corneas (26). The appearance of these fibrils in electron micrographs along with amino acid sequence data suggests that type V collagen molecules may occur within a heterotypic type I + V collagen fibril.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…We observed collagen fibrils with an ordered and regular barbed appearance in the myometrium (Fig. 2B), which resembles that observed in chick corneas (26). The appearance of these fibrils in electron micrographs along with amino acid sequence data suggests that type V collagen molecules may occur within a heterotypic type I + V collagen fibril.…”
Section: Discussionmentioning
confidence: 50%
“…In addition to the effect of procollagen processing and glycosylation of collagen molecules and collagen-proteoglycan interactions on the formation of fibrils, it has been shown that the interaction of two or more different types of fibrillar collagen chains may interact and result in the formation of heterotypic fibrils (23)(24)(25)(26). We observed collagen fibrils with an ordered and regular barbed appearance in the myometrium (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…It is the proteolytically trimmed amino-terminal globular sequences of the minor fibrillar collagen chains that are thought to regulate the shapes and diameters of heterotypic fibrils (Linsenmayer et al, 1993). Thus, proteolytic trimming of the amino-terminal globular sequences of minor fibrillar procollagen chains appears to be another way in which the BMP1/ TLD-like proteinases regulate collagen fibrillogenesis.…”
Section: Fibrillar Collagensmentioning
confidence: 99%
“…In the secondary corneal stroma, the small diameters of the collagen fibrils are thought to result from the incorporation of a relatively large proportion of type V collagen into heterotypic type I + V fibrils (Doane et al, 1992;Birk et al, 1990); control of fibril diameter is 43 thought to be exerted by the presence of a large aminoterminal globular domain of type V (Linsenmayer et al, 1993) that serves to inhibit lateral growth of the fibril. It is reasonable to assume that fibril diameter in the primary stroma is controlled in a similar fashion, but by a different collagen type (see below): these fibrils contain, along with type I collagen, type I1 collagen instead of type V.…”
Section: Introductionmentioning
confidence: 99%